2023
DOI: 10.1002/adma.202205714
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Strain Engineering on Van der Waals 2D Materials: Tunable Electrical, Electrochemical, Magnetic, and Optical Properties

Abstract: counterparts. [2] Therefore, 2D materials are ideal for flexible optoelectronics and have the potential to be used in the next-generation ultrathin electronic and optoelectronic devices. [1] The concept of 2D materials was first realized when graphene was found in 2004. [4] Graphene has attracted extensive attention for its excellent electrical, optical, and mechanical properties. [4][5][6] They have been investigated for various technological applications, including spintronics, sensors, optoelectronics, supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 140 publications
1
34
0
Order By: Relevance
“…Since even small changes of bonding angle and length can be efficiently tuned by strain engineering technique, which can lead to a dramatic change in the band structure and electronic correlation interactions, [80][81][82][83][84] the strain and mechanical deformation in layered 3d-orbital materials can have a profound effect on the magnetic exchange interactions J between neighboring local magnets and the corresponding magnetic ground state therein. Technically, strain can be applied to the targeted nanoflake by a variety of means, including substrate surface topography modification, thermal expansion mismatch, strain relaxation and other methods.…”
Section: Strain Engineering For Enhancing Exchange Interactions Of Ma...mentioning
confidence: 99%
“…Since even small changes of bonding angle and length can be efficiently tuned by strain engineering technique, which can lead to a dramatic change in the band structure and electronic correlation interactions, [80][81][82][83][84] the strain and mechanical deformation in layered 3d-orbital materials can have a profound effect on the magnetic exchange interactions J between neighboring local magnets and the corresponding magnetic ground state therein. Technically, strain can be applied to the targeted nanoflake by a variety of means, including substrate surface topography modification, thermal expansion mismatch, strain relaxation and other methods.…”
Section: Strain Engineering For Enhancing Exchange Interactions Of Ma...mentioning
confidence: 99%
“…Magnetism in two-dimensional (2D) van der Waals (vdW) materials has attracted enormous attention in technological advances as its potential application ranges from topological magnonics to low-power spintronics and quantum computing. Among the families of 2D vdW materials, Fe 5 GeTe 2 (F5GT) is a newly synthesized and promising vdW ferromagnet for spintronic devices due to its high Curie temperature (about 293 K) and novel spintronic properties. , Strain engineering is an exciting and feasible method to manipulate the properties of materials in both theoretical and experimental investigations, which creates various opportunities for the study of new fundamental physics and applications of 2D vdW materials. Meanwhile, 2D vdW materials were often transferred or grown onto a substrate such that the strain can be introduced by the substrate . It has been observed that the magnetic properties of vdW materials are sensitive to the applied strain. …”
Section: Introductionmentioning
confidence: 99%
“…2−5 These materials have excellent physical and chemical properties and flexibility through the two-dimensional van der Waals layered structure and strong valent bonding between atoms. 6,7 In addition to graphene, many materials share the unique properties of 2D materials, such as hexagonal boron nitride (h-BN), black phosphorus, and transition metal dichalcogenides (TMDCs). 8−10 Among these 2D materials, TMDCs, which are band gap-tunable and have good photoelectrical properties, are attracting attention and have been researched in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials emerged in 2004 when Andre Gaim and Konstantin Novoselov separated graphene from graphite through exfoliation . Since then, various two-dimensional materials have been discovered and examined, all of which are strongly and covalently bonded to layers on the same plane but weakly bonded by van der Waals forces with other layers. These materials have excellent physical and chemical properties and flexibility through the two-dimensional van der Waals layered structure and strong valent bonding between atoms. , In addition to graphene, many materials share the unique properties of 2D materials, such as hexagonal boron nitride (h-BN), black phosphorus, and transition metal dichalcogenides (TMDCs). Among these 2D materials, TMDCs, which are band gap-tunable and have good photoelectrical properties, are attracting attention and have been researched in recent years. , TMDC materials including MoS 2 , WS 2 , MoSe 2 , and WSe 2 are used in various optoelectronic devices due to high mobility and the change in band gap characteristics according to atomic-scale thickness control. Moreover, tin disulfide (SnS 2 ), which is a post-TMDC, is attracting attention due to a layered structure similar to that of TMDCs and has excellent photoelectric characteristics. , The high optical transmittance, electrical conductivity, and band gap of SnS 2 nanosheets make it suitable for use in various photoelectric devices and electrocatalysts. , Recently, attempts have been made to improve its photometric characteristics and to add magnetic properties by doping nanosheet SnS 2 with metals, such as Fe, Mo, W, Ru, and Zn. Changes in its band gap, electrical, and magnetic properties using substitutional doping with other metal elements in Sn ion sites have also been studied using density functional theory. , The band gap of SnS 2 can be engineered through doping; optical and electrical properties of doped nanosheet SnS 2 provide improved photodynamic activity compared with pristine SnS 2 . In particular, Zn 2+ ions have an ionic radius of 0.074 nm, which is similar to that of Sn 4+ (0.071 nm), and therefore can be easily substituted for the Sn 4+ site, and thus, Zn is an excellent doping element and is relatively feasible for the synthesis process. However, most research into the tuning of opto-electronic properties of tin sulfide nanosheet thin films through the doping process was conducted using simulation study to calculate theoretical values or spray pyrolysis methods, creating a need for experimental results obtained through a synthesis process at atomic scales using precisely controlled methods.…”
Section: Introductionmentioning
confidence: 99%